Avaliação de três estratégias de aleitamento com leite de descarte no desempenho de bezerras mestiças Holandês x Gir - Juliana Mergh Leao (2013)
The effects of three milk feeding strategies were evaluated in 33 females Holstein x Gir calves. The strategies were: Group 1 - 6L-30d/4L-60d/2L-90 days, Group 2 - 6L-45d/4L-60d/2L-90 days and Group 3 - 8L-30-d/6L-60d/3L-90 days using waste milk with 110g / kg DM of total solids. All calves were weaned at 90 days of age. Water and starter were provided ad libitum. A completely randomized design was used for statistical analysis. Starter intake, body weight, weight gain, feed efficiency and plasma glucose concentrations were analyzed in split plot, with the feeding strategies on the plots and in the sub-plots ages of evaluation. Means were tested with Tukey and SNK (P=0.06). Initial weights and total protein werent different (P>0.05). Milk intake in the first couple of weeks was lower than offered. There was interaction between starter intake and days evaluated and dry matter intake increased with age (P<0.05). There was also interaction between average daily gain (g/day) and days evaluated (P<0.06). Plasma glucose concentrations were different between the strategies (P<0.05), but considered normal in the range. The best feeding strategy was used in Group 1 - 6L-30d/4L-60d/2L-90 days, which obtained at 90 days of age (2358,55 ± 287,98 g/d of DMI), similar starter intake to group 2 (2177,26 ± 375,40 g/d of DMI) (P>0.05) and higher than 3 (P<0.05) (1984,10 ± 341,97 g/d of DMI), glucose concentration in the normal range, average daily gain (Group 1: 906,90 ± 155,05 g/d) similar to groups 2 and 3 (778,64 ± 205,23 g/d e 951,00 ± 187,36 g/d, respectively) and lowest cost/kg in weight gain (Group 1: R$ 6,17, Group 2: R$ 6,55 and Group 3: R$ 7,31).